Development of an alpha dust monitor using a GPS scintillator plate. (March 2019) - Morishita, Yuki; Kaneko, Junichi H.; Higuchi, Mikio; Izaki, Kenji; Yajima, Tatsuo; Matsuura, Mitsugu; Tamura, Ken; Torii, Tatsuo
Abstract : A dust monitor with a silicon surface barrier detector (SSBD) is introduced at a nuclear fuel facility to detect airborne contamination of 238 Pu and 239 Pu released by past accidents. However, an SSBD frequently produces false alarms, especially in a room with high humidity. To develop a highly reliable dust monitor, we developed an alpha-particle spectrometer based on a cerium-doped Gd2 Si2 O7 (GPS) scintillator plate and a photomultiplier tube (PMT). The GPS scintillator plate is hexagonal and 50 mm in diameter, and the scintillator layer is approximately 40 μm. An output signal from the PMT is amplified by a preamp and transferred to an MCA. Then, an energy spectrum is displayed in real time. The 241 Am alpha source, Rn progeny collected on the air filter, and a PuO2 particle were measured by our developed spectrometer. The energy resolution for 5.5-MeV alpha particles was ∼11.9% ± 0.2% of the FWHM. The efficiency was 92%, and it had a uniform sensitivity. By applying an energy window, the count-rate of the Rn progeny decreased by 77%. The GPS scintillator plate was able to measure the alpha spectrum even though the GPS scintillator got wet. Therefore, the alpha dust monitor using the GPS scintillator plate is ideal for detecting alpha-particle emitters in places lacking temperature and humidity controls, such as the outside of buildings. Highlights: An alpha dust monitor using a GPS scintillator plate was successfully developed. The energy resolution for 5.5-MeV alpha particles was ∼11.9% ± 0.2% of the FWHM. The count-rate of the Rn progeny decreased by 77% by applying an energy window. The alpha dust monitor was capable of conducting alpha-particle spectroscopy even though the GPS scintillator got wet. The alpha dust monitor is an ideal choice for in places lacking temperature and humidity controls.